Diseño de adaptaciones curriculares en la educación superior para estudiantes con discapacidad visual de la Universidad Nacional de Loja, período 2024. - Puertas Gallardo, Edwin Eduardo (2024)
This research on the design of curricular adaptations for visually impaired students who study at Universidad Nacional de Loja contributes to the research field of higher education since, at this educational level, there are many issues that must be addressed to successfully develop an inclusive process. The present research was carried out at Universidad Nacional de Loja during the period March-August 2024; its objectives were to characterize the design of curricular adaptations by teachers, identify the challenges and barriers teachers face when making curricular adaptations, and put forward a proposal that allows to overcome the problem of this research study. The methodology used was descriptive and transversal, with a mixed approach, as both quantitative and qualitative information was collected, integrated and analyzed, applying inductive, deductive, analytical, and synthetic methods. In addition, techniques such as the survey through a questionnaire aimed at teachers as well as a semi-structured interview with the University Welfare staff were applied. The significant findings indicate that 35.4% of teachers have not received specific training on curricular adaptations, 14.6% sometimes collaborate with other professionals to design them, 22.9% consider the lack of institutional support, and 47.4% point out the absence of guides, protocols, or institutional manuals as barriers that prevent the proper design of curricular adaptations. Based on these results, a proposal focused on generating a manual of strategies for designing curricular adaptations for visually impaired students was made. This manual is structured for the learning components in contact with the teacher, practical-experimental and autonomous, in accordance with the curricular structure maintained by Universidad Nacional de Loja.